Long-term development of training characteristics and physiological determinants in world-leading and medal-winning female cross-country skiers: a three decade comparative analysis - Staff, H.; Solli, G. S.; Welde, B.; Tønnessen, E.; Sandbakk, Ø. (Sports Medicine - Open, 2025)
Background This study describes the long-term development of training characteristics and physiological performance-determining variables among six world-class (Tier 5) female cross-country skiers across three decades, collectively holding 61 Olympic/World Championship medals.